Predictive assessment of climate change impact on water yield in the Meta River Basin, Colombia: An InVEST model application - Valencia, Jhon B.; Guryanov, Vladimir V; Mesa Diez, Jeison; Diaz, Nilton; Escobar Carbonari, Daniel; Gusarov, Artyom V. (MDPI, 2024)
This paper presents a hydrological assessment of the 113,981 km2 Meta River basin in Colombia using 13 global climate models to predict water yield for 2050 under two CMIP6 scenarios, SSP 4.5 and SSP 8.5. Despite mixed performance across subbasins, the model was notably effective in the upper Meta River subbasin. This study predicts an overall increase in the basin’s annual water yield due to increased precipitation, especially in flatter regions. Under the SSP 4.5, the Meta River basin’s water flow is expected to rise from 5141.6 m3/s to 6397.5 m3/s, and to 6101.5 m3/s under the SSP 8.5 scenario, marking 24% and 19% increases in water yield, respectively. Conversely, the upper Meta River subbasin may experience a slight decrease in water yield, while the upper Casanare River subbasin is predicted to see significant increases. The South Cravo River subbasin, however, is expected to face a considerable decline in water yield, indicating potential water scarcity. This study represents a pioneering large-scale application of the InVEST–AWY model in Colombia using CMIP6 global climate models with an integrated approach to produce predictions of future water yields.